Personalized designs of adjuvant radiotherapy for pancreatic cancer based on molecular profiles. Issue 1 (7th November 2020) - Zhu, Xiaofei; Cao, Yangsen; Ju, Xiaoping; Zhao, Xianzhi; Jiang, Lingong; Ye, Yusheng; Shen, Yuxin; Cao, Fei; Qing, Shuiwang; Zhang, Huojun
Abstract: This study aims to identify postoperative recurrence patterns of pancreatic cancer with different molecular profiles, which provides evidence for personalized target volumes of adjuvant radiotherapy. Patients with pathologically confirmed resectable pancreatic ductal adenocarcinoma were included. Recurrences were treated with stereotactic body radiation therapy. Immunohistochemical staining of Ki‐67, P53, and programmed cell death‐ligand 1 (PD‐L1) was carried out. Both of the intensities of Ki‐67 and P53 were classified as 10% or less, 11%‐49%, and 50% or more. Eighty‐nine patients had PD‐L1 tested, stratified as TC0 and IC0, and TC1/2 or IC1/2. Distances with significant differences among different levels or beyond 10 mm were of interest. With the increasing intensity of Ki‐67, the distance from the superior and posterior border of 80% recurrences to the celiac axis (CA) ranged from 10.1 to 13.8 mm and 9.2 to 11.0 mm. The distance from the inferior and posterior border of 80% recurrences to the superior mesenteric artery (SMA) ranged from 9.4 to 9.9 mm and 9.4 to 11.0 mm. Similarly, with the increasing intensity of P53, the distance from the superior and posterior border of 80% recurrences to the CA ranged from 9.7 to 13.2 mm and 10.1 to 10.6 mm. The distance from the inferior and anterior border of 80% recurrences to the SMA ranged from 9.5 to 9.9 mm and 8.6 to 9.4 mm. Regarding the increasing level of PD‐L1, the distance from the superior border of 80% recurrences to the CA ranged from 10.9 to 13.5 mm. A biologically effective dose of more than 65 Gy to local recurrences was predictive of favorable outcomes in all levels of Ki‐67, P53, and PD‐L1. Nonuniform expansions of regions of interest based on different levels of molecular profiles to form target volumes could cover most recurrences, which might be feasible for adjuvant radiotherapy. Abstract : This study aims to provide evidence of personalized target volume delineations and dose prescriptions of adjuvant radiotherapy for pancreatic cancer based on molecular profiles, including Ki‐67, P53, and programmed cell death‐ligand 1 (PD‐L1). In the case of different levels of these 3 molecular biomarkers, nonuniform expansions, beyond 10 mm, to form target volumes were required to cover most recurrences. Additionally, a high dose regardless of levels of Ki‐67, P53, and PD‐L1 was conducive to improved survival.